Using information technology : - Sawyer, Stacey C. (McGraw-Hill Technology Education, 2005)
"Using Information Technology, 6/e" covers the fundamental computing concepts that are part of the digital age, including software, hardware, data, people, and procedures. The text centers on educating today's technology consumer, using themes of ethics, the Internet, and communications to demonstrate how the changing world of technology influences our lives and the decisions we make.